Al4SiC4 composition or Al4SiC4 powder

JP7651668B2Active Publication Date: 2025-03-26TYK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023215379
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-03-26
Estimated Expiration
2041-03-08

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、Al4C3を実質的に含まず、かつ硫黄を実質的に含まないAl4SiC4組成物又はAl4SiC4粉末を提供することができる。Al4C3を実質的に含まず、かつ硫黄を実質的に含まないので、本発明のAl4SiC4粉末を耐火物に添加しても、耐火物が体積膨張してその形状安定性を損なうのを防止できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651668000003
    Figure 0007651668000003
  • Figure 0007651668000004
    Figure 0007651668000004
  • Figure 0007651668000005
    Figure 0007651668000005
Patent Text Reader

Abstract

To provide an Al4SiC4 composition or Al4SiC4 powder that is substantially free of Al4C3 and substantially free of sulfur.SOLUTION: This invention relates to an Al4SiC4 composition or Al4SiC4 powder, wherein: a ratio IAl4C3 / IAl4SiC4 of an integrated intensity IAl4C3 (cps_deg) of a diffraction peak of Al4C3 at around 2θ=55.1° to an integrated intensity IAl4SiC4 (cps_deg) of the diffraction peak of Al4SiC4 at around 2θ=56.0°, measured by powder X-ray diffraction, is 0.1% or less; a sulfur content is 150 mass ppm or less; and a crystal size calculated from the diffraction peak of Al4SiC4 around 2θ=31.7°, measured by the powder X-ray diffraction, is 1,000 to 1,500 Å.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Al4SiC4 composition or an Al4SiC4 powder. [Background technology]

[0002] Al4SiC4 is a carbide made of aluminum and silicon, and has been attracting attention in recent years as a new functional additive for carbon-containing refractories. The effect of adding Al4SiC4 is said to be the densification of the refractory structure. It is presumed that the densification of the refractory structure occurs when Al4SiC4 present in the refractory structure reacts with CO gas in the atmosphere. That is, as shown in formula (1), it is presumed that this is brought about by the generation of gas containing Al from Al4SiC4 at high temperatures, which diffuses into the voids in the refractory structure, reacts with CO gas, condenses again as Al2O3, and fills the voids.

[0003] Al4SiC4+6CO→2Al2O3+SiC+9C (1)

[0004] As a method for producing Al4SiC4, Non-Patent Document 1 discloses a method in which an aluminum source, a silicon source, and a carbon source as starting materials are mixed, and the mixed materials are fired in an inert gas atmosphere to synthesize Al4SiC4.

[0005] The synthesis of Al4SiC4 is believed to take place in the following two stages: First, as the temperature rises due to heating, Al4C3 and SiC are produced as shown in equations (2) and (3), and then, at temperatures above 1300°C, Al4C3 and SiC react to produce Al4SiC4 as shown in equation (4).

[0006] 4Al+3C → Al4C3(2) Si+C→SiC (3) Al4C3+SiC→Al4SiC4(4) [Prior art documents] [Patent documents]

[0007] [Non-Patent Document 1] Journal of the Ceramic Society of Japan 115

[11] 761-766(2007) Summary of the Invention [Problem to be solved by the invention]

[0008] However, in the conventional manufacturing method of Al4SiC4, the obtained Al4SiC4 powder contains Al4C3, a by-product of the synthesis of Al4SiC4, as an impurity. Al4C3 is easily hydrated, and when Al4SiC4 powder containing Al4C3 is added to a refractory, the Al4C3 hydrates and expands in volume, impairing the shape stability of the refractory.

[0009] In addition, in the conventional manufacturing method of Al4SiC4, the obtained Al4SiC4 powder contains sulfur derived from the carbon source of the starting material. When sulfur-containing Al4SiC4 powder is added to a refractory, the refractory expands in volume and loses its shape stability. This is because the sulfur present in trace amounts in the carbon source of the starting material reacts with Al during the synthesis of Al4SiC4, producing Al2S3 and the like. Al2S3 and the like are easily hydrated, and when Al4SiC4 powder containing Al2S3 and the like is added to a refractory, the refractory expands in volume and loses its shape stability.

[0010] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide an Al4SiC4 composition or Al4SiC4 powder that is substantially free of Al4C3 and substantially free of sulfur. [Means for solving the problem]

[0011] In order to solve the above problem, one aspect of the present invention is to provide a method for producing a powder X-ray diffraction pattern by using an integrated intensity I Al4C3 (cps·deg) and the integrated intensity of the diffraction peak of Al4SiC4 at 2θ=56.0° I Al4SiC4 (cps deg) IAl4C3 / I Al4SiC4 The Al4SiC4 composition or Al4SiC4 powder has a content of 0.1% or less and a sulfur content of 150 mass ppm or less, and has a crystallite size of 1000 to 1500 Å calculated from the diffraction peak of Al4SiC4 near 2θ=31.7° measured by powder X-ray diffraction. Effect of the Invention

[0012] According to the present invention, an Al4SiC4 composition or Al4SiC4 powder that is substantially free of Al4C3 and substantially free of sulfur can be provided. Since the composition or powder is substantially free of Al4C3 and substantially free of sulfur, even if the Al4SiC4 powder of the present invention is added to a refractory, the refractory can be prevented from expanding in volume and losing its shape stability.

[0013] The large crystallite size indicates that the crystal morphology is growing. Al4SiC4 particles with such a crystallite size have enhanced hydration resistance. Therefore, the functionality in the refractory structure is less likely to decrease. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a diagram illustrating the pre-heating treatment of the carbon source in this embodiment (FIG. 1(a) shows the state in which the carbon source is placed in an inner container, and FIG. 1(b) shows the state in which the inner container is embedded in coke particles). [Diagram 2] 1 is a chart obtained by X-ray diffraction analysis of the Al4SiC4 powder produced in Example 1. [Diagram 3] FIG. 3 is an enlarged view of the horizontal axis of the chart in FIG. 2 from 50° to 60°. [Figure 4] FIG. 3 is an enlarged view of the horizontal axis of the chart in FIG. 2 from 20° to 30°. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the Al4SiC4 composition or Al4SiC4 powder according to the embodiment of the present invention and the manufacturing method thereof will be described in detail with reference to the accompanying drawings. However, the present invention can be embodied in various forms and is not limited to the embodiments described in the present specification. The present embodiment is provided with the intention of enabling a person skilled in the art to fully understand the invention by fully disclosing the specification. (Al4SiC4 composition or Al4SiC4 powder)

[0016] First, the Al4SiC4 composition or Al4SiC4 powder will be described. The Al4SiC4 composition is obtained by firing a mixture containing an aluminum source, a silicon source, and a carbon source. The Al4SiC4 powder is obtained by pulverizing the Al4SiC4 composition.

[0017] The Al4SiC4 composition or Al4SiC4 powder of this embodiment does not substantially contain Al4C3. Specifically, the integrated intensity I of the diffraction peak of Al4C3 at around 2θ=55.1° measured by powder X-ray diffraction Al4C3 (cps·deg) and the integrated intensity of the diffraction peak of Al4SiC4 at 2θ=56.0° I Al4SiC4 (cps deg) I Al4C3 / I Al4SiC4 is 0.1% or less, preferably 0.05% or less, and more preferably, no diffraction peak of Al4C3 is observed near 2θ=55.1°.

[0018] When Al4C3-containing Al4SiC4 powder is added to a refractory, Al4C3 is hydrated and expands in volume, impairing the dimensional stability of the refractory. Al4C3 / I Al4SiC4 is less than 0.1%.

[0019] Among the information obtained from powder X-ray diffraction, the area occupied by the waveform of the diffraction peak is the integrated intensity. The integrated intensity is the product of the diffraction angle of the sample in the powder and the geometric probability of the existence of a certain crystal grain (peak height). By calculating the ratio of the integrated intensities, it is possible to quantitatively evaluate the probability of the existence of a certain crystal grain. Here, the ratio of graphite remaining in the Al4SiC4 powder can be quantitatively analyzed, and the ratio of Al4C3 remaining in the Al4SiC4 powder can be quantitatively analyzed.

[0020] Powder X-ray diffraction was carried out under the following conditions. [Table 1]

[0021] The powder X-ray diffraction using CuKα radiation was performed using RINT2000 manufactured by Rigaku Corporation, and the measured diffraction intensity was plotted on a graph with the X-ray incidence angle 2θ (°) on the horizontal axis and the diffraction intensity (cps) on the vertical axis. The integrated intensity (cps deg) was calculated using "Integrated Powder X-ray Analysis Software PDXL" ver.2.7.3.0 manufactured by Rigaku Corporation.

[0022] The Al4SiC4 composition or Al4SiC4 powder of this embodiment does not substantially contain sulfur. Specifically, the sulfur content (sulfur element and sulfur in sulfur compounds such as Al2S3) is 150 mass ppm or less, desirably 130 mass ppm or less, and more preferably 100 mass ppm or less.

[0023] When sulfur-containing Al4SiC4 powder is added to a refractory, the refractory expands in volume and loses its shape stability. This is because a trace amount of sulfur present in the carbon source of the starting material reacts with Al during the synthesis of Al4SiC4 to produce Al2S3. Al2S3 is easily hydrated, and when Al4SiC4 powder containing Al2S3 is added to a refractory, the refractory expands in volume and loses its shape stability. For this reason, in this embodiment, the sulfur content contained in the Al4SiC4 composition or Al4SiC4 powder is 150 mass ppm or less.

[0024] The sulfur content was measured using the combustion-infrared absorption method, specifically, a material carbon and sulfur analyzer (Horiba, EMIA-810). When the sample was burned at high temperature in an oxygen stream, the sulfur contained in the sample was gasified and extracted as sulfur dioxide. The extracted sulfur dioxide was measured with an infrared detector, and the measured sulfur dioxide value was converted to the sulfur content in the sample. This method for quantifying the sulfur content is standardized in JIS R 2016-2:2009.

[0025] The Al4SiC4 composition or Al4SiC4 powder of the present embodiment is preferably substantially free of graphite. Specifically, the integrated intensity I G (cps·deg) and the integrated intensity of the diffraction peak of Al4SiC4 at 2θ=56.0° I Al4SiC4 (cps deg) I G / I Al4SiC4 is 0.01% or less, preferably 0.005% or less, and more preferably, no graphite diffraction peak is observed near 2θ=26.5°.

[0026] Graphite originates from the carbon source of the starting material. Graphite has oxidation resistance up to around 1000°C. When Al4SiC4 powder containing graphite is added to a refractory, the reactivity of Al4SiC4 decreases. Since the densification of the refractory structure occurs when Al4SiC4 reacts with an oxidizing gas (CO gas), the effect of adding Al4SiC4 is hindered when graphite coexists with Al4SiC4. For this reason, in this embodiment, the I measured by powder X-ray diffraction is G / I Al4SiC4 is less than 0.01%.

[0027] The Al4SiC4 composition or Al4SiC4 powder of this embodiment desirably has a large crystallite size. Specifically, the crystallite size calculated from the diffraction peak of Al4SiC4 at about 2θ=31.7° measured by powder X-ray diffraction is 1000 to 1500 Å, more preferably 1100 to 1500 Å, and further preferably 1100 to 1450 Å.

[0028] Large crystallite size indicates that the crystal form is growing. Al4SiC4 particles with such crystallite size have enhanced hydration resistance. Therefore, the functionality in the refractory structure is less likely to decrease. If the crystallite size is too large, the functionality (reactivity with CO gas) decreases, so 1000 to 1500 Å is optimal.

[0029] The crystallite size of Al4SiC4 is calculated by measuring the half-width of the diffraction peak at about 2θ=31.74° in powder X-ray diffraction using CuKα radiation and using Scherrer's formula. Specifically, the crystallite size was calculated using "Integrated Powder X-ray Analysis Software PDXL" ver.2.7.3.0 manufactured by Rigaku Corporation.

[0030] The particle diameter of the Al4SiC4 powder of this embodiment is not particularly limited, but in the volume-based particle size distribution, the difference between the cumulative 90% particle diameter and the cumulative 10% particle diameter is divided by the cumulative 50% particle diameter (D 90 -D 10 ) / D 50 : The particle size distribution span value is preferably 1.7 to 2.5.

[0031] The particle size distribution span value is set to 1.7 to 2.5 from the viewpoint of defining the range (width) of the particle size distribution. If it is less than 1.7, the particle size distribution range is narrow, and there is a problem that the particles are easily aggregated, whereas if it is 1.7 or more, aggregation is suppressed and the performance as an additive is well exhibited. On the other hand, if it exceeds 2.5, there is a problem that the ratio of coarse particles and fine particles increases, affecting the performance as an additive. The optimal particle size distribution span value is 1.7 to 2.5, preferably 1.8 to 2.4.

[0032] The range of actual particle size distribution (D0 to D 100 ) is 7 to 350 μm. Based on this, the D 90 -D 10 (Width of particle size distribution) can be specified. 50 The thickness is in the range of 7 to 350 μm, preferably 30 to 120 μm.

[0033] The volume-based cumulative 10% particle size, cumulative 50% particle size, and cumulative 90% particle size are measured by a laser diffraction scattering method. The method for measuring particle size distribution by the laser diffraction scattering method is standardized in JIS R 1629:1997. Specifically, the measurements were performed using a laser diffraction scattering particle size distribution measuring device MT3000II manufactured by Nikkiso Co., Ltd. Distilled water was used as the solvent, and the powder was dispersed with ultrasonic waves in a sample circulator that comes standard with the device, after which the particle size was measured. (Method of manufacturing Al4SiC4 composition or Al4SiC4 powder)

[0034] Next, a method for producing the Al4SiC4 composition or Al4SiC4 powder will be described.

[0035] As starting materials, an aluminum source, a silicon source, and a carbon source are used.

[0036] The aluminum source may be metal Al, aluminum oxide, aluminum hydroxide, etc. From the standpoint of purity and production efficiency, it is preferable to use metal Al powder.

[0037] The silicon source can be metal Si or silicon dioxide. Metal Si powder is preferable from the viewpoint of purity and production efficiency. Al-Si alloy powder can also be used as the aluminum source and silicon source.

[0038] At least a part of the carbon source is a heat-treated carbon source that has been preheat-treated in coke particles, and carbon black is used as the heat-treated carbon source.

[0039] The pre-heating treatment in the coke granules will be explained. As shown in Fig. 1(a), carbon black 1 is placed in an inner container 2 such as a crucible and covered with a lid 2a. As shown in Fig. 1(b), the inner container 2 is placed in an outer container 3 such as a crucible and buried in coke granules 4 such as coke breeze. The outer container 3 is then placed in a heating furnace and heated under an argon gas atmosphere, allowing the heat treatment in the coke granules 4 to be performed.

[0040] Carbon black is an artificial carbon with high industrial value, and is a material that is likely to be supplied stably in the future. Some types of carbon black have a relatively low sulfur content. By pre-heating such carbon black, the sulfur content can be further reduced. The reason for this is that the free sulfur present in the carbon black is oxidized at high temperatures by oxygen contained in the carboxyl and hydroxyl groups, which are the surface functional groups of the carbon black particles, and is gasified and removed. On the other hand, the sulfur present in the molecules that make up the carbon black is difficult to gasify and remove even with the above-mentioned method, so it tends to remain.

[0041] In addition to carbon black, graphite such as scaly graphite and artificial graphite can also be used as the heat-treated carbon source. However, naturally occurring graphite is unevenly distributed, and artificial graphite has a limited range of industrial uses, making it a less versatile raw material. When graphite is used as the carbon source, graphite diffraction peaks are observed in powder X-ray diffraction. By using carbon black that has been pre-heat-treated as the carbon source, the graphite diffraction peaks can be reduced; specifically, the integrated intensity I G and Al4SiC4 diffraction peak integral intensity I Al4SiC4 Ratio to I G / I Al4SiC4 can be reduced to less than 0.01%.

[0042] The carbon source preferably contains 80 mass% to 100 mass% of the above-mentioned carbon black that has been subjected to a preheating treatment as a main material. By using carbon black as a main material of the carbon source, the diffraction peak of graphite can be effectively reduced.

[0043] The carbon source desirably contains 20 mass% or less of a secondary material composed of at least one of coke (preferably petroleum coke), expanded graphite, or activated carbon. Petroleum coke and activated carbon are carbon with a porous particle surface. Expanded graphite is graphite with expanded interlayers. Petroleum coke, expanded graphite, and activated carbon all have a porous surface, so they can promote the synthesis reaction of Al4SiC4 and make it difficult for Al4C3 to remain. If there is no Al4C3 remaining, the synthesis yield of Al4SiC4 improves. In addition, petroleum coke, expanded graphite, and activated carbon have a higher sulfur content than carbon black, so they are blended so that the sulfur content after synthesis does not exceed 150 mass ppm. It is possible to preheat-treat petroleum coke, expanded graphite, and activated carbon, but even if they are preheat-treated, the sulfur content cannot be reduced as much as carbon black.

[0044] The aluminum source, silicon source, and carbon source are weighed in amounts such that the molar ratio of aluminum, silicon, and carbon contained therein is 4:1:4.

[0045] Next, the aluminum source, silicon source, and carbon source are mixed using a mixer such as a dry Henschel mixer. The mixing time is not particularly limited, but it is preferable to mix for 5 minutes or more in order to thoroughly mix the raw materials.

[0046] Next, the mixed raw material is loaded into a crucible, and the crucible is placed in a batch furnace such as a resistance heating furnace or a tubular furnace, or a continuous furnace such as a tunnel furnace, and the mixed raw material is fired in an inert gas atmosphere at a temperature of 1650 to 1900° C. for 1 to 10 hours.

[0047] Al4SiC4 is synthesized by firing. The synthesis of Al4SiC4 is carried out in the following two stages. That is, as the temperature rises during firing, Al4C3 and SiC are first produced as shown in formulas (2) and (3), and then at 1300°C or higher, Al4C3 and SiC react to produce Al4SiC4 as shown in formula (4). At temperatures below 1650°C, Al4C3 is likely to remain after the reaction, while at temperatures above 1650°C, the production of Al4SiC4 is significantly promoted. At firing temperatures above 1900°C, part of Al4SiC4 will thermally decompose, so a temperature of 1900°C or lower is desirable.

[0048] 4Al+3C → Al4C3(2) Si+C→SiC (3) Al4C3+SiC→Al4SiC4(4)

[0049] By mixing the aluminum source, silicon source, and carbon source in the above molar ratio and firing the mixed raw material at the above temperature for the above time, Al4C3 can be reduced. Specifically, the integrated intensity I Al4C3 (cps·deg) and the integrated intensity of the diffraction peaks of Al4SiC4 I Al4SiC4 (cps deg) I Al4C3 / I Al4SiC4 can be reduced to less than 0.1%.

[0050] After synthesis of Al4SiC4, the crucible is removed from the furnace, and the Al4SiC4 composition is taken out from the crucible. The Al4SiC4 composition is dry-pulverized in a roll crusher to obtain Al4SiC4 powder. (Industrial Applicability)

[0051] The Al4SiC4 powder of this embodiment does not contain sulfur-containing compounds such as Al4C3 and Al2S3 that are quenchable by moisture, and does not contain graphite that reduces the reactivity of Al4SiC4. The Al4SiC4 powder of this embodiment can be used as a functional additive for improving the shape stability, strength improvement, and infiltration resistance of carbon-containing refractories. The Al4SiC4 powder of this embodiment is not limited to being used as a functional additive for carbon-containing refractories, and can also be used, for example, as an antioxidant. EXAMPLES

[0052] Example 1 Metallic Al powder (-75μm), metallic Si powder (-45μm), and pre-heated carbon black (60~280nm) were mixed in a theoretical molar ratio of Al:Si:C=4:1:4 and mixed for 10 minutes in a dry Henschel mixer. The mixed raw materials were loaded into a crucible, heated to 1800℃ in an argon gas stream, and held at 1800℃ for 10 hours.

[0053] The power to the furnace was turned off and the crucible was allowed to cool to ambient temperature. After cooling, the crucible was removed from the furnace, the Al4SiC4 composition was removed from the crucible, and the Al4SiC4 composition was dry crushed in a roll crusher.

[0054] The physical properties of the obtained Al4SiC4 powder were measured by powder X-ray diffraction in accordance with the method described above.

[0055] Figure 2 is a chart obtained by X-ray diffraction analysis of Al4SiC4 powder. The horizontal axis is the incident angle 2θ (unit: °), and the vertical axis is the diffraction intensity (unit: cps).

[0056] Figure 3 is an enlarged view of the horizontal axis of the chart in Figure 2 from 50° to 60°. No diffraction peak of Al4C3 was observed near 2θ=55.1°, and I Al4C3 / I Al4SiC4 The diffraction peak of graphite was not observed near 2θ=26.5°. G / IAl4SiC4 was 0.

[0057] The characteristic X-rays generated from a Cu target were used as the X-ray source for the measurements. There are Kα and Kβ characteristic X-rays, and Kα is further divided into Kα1 and Kα2. The X-rays used for the measurements are Kα1. Kβ appears as a satellite to the strongest peak at 31.7°. In this measurement, most of the peaks can be removed by attaching a cut filter, but if the strength of the X-ray source and the detector sensitivity of this measurement device are high, the Kβ originating from the X-rays appears as a small peak as shown in Figure 2. As shown in Figure 3, the peak originating from Kα2 begins to separate at about half the height from the main peak Kα1 at higher angles.

[0058] The sulfur content of the obtained Al4SiC4 powder was 90 ppm. The crystallite size calculated from the Al4SiC4 diffraction peak at 2θ = 31.7° was 1147 Å. In the volume-based particle size distribution, (D 90 -D 10 ) / D 50 The particle size distribution span value was 2.1. Example 2

[0059] Needle coke was added as a secondary carbon source at 5 mass%. That is, the carbon source was 95 mass% of pre-heat-treated carbon black and 5 mass% of needle coke. Other than this, Al4SiC4 powder was obtained using the same method as in Example 1.

[0060] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 140 ppm, the crystallite size was 1157 Å, and the particle size distribution span value was 2.0. Example 3

[0061] Needle coke was added as a secondary carbon source at 20 mass%. That is, the carbon source was 80 mass% of pre-heated carbon black and 20 mass% of needle coke. Other than this, Al4SiC4 powder was obtained using the same method as in Example 1.

[0062] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 140 ppm, the crystallite size was 1118 Å, and the particle size distribution span value was 2.0. Example 4

[0063] 5 mass% of expanded graphite was added as a secondary material of the carbon source. That is, the carbon source was 95 mass% of pre-heat-treated carbon black and 5 mass% of expanded graphite. Other than this, the same method as in Example 1 was used to obtain Al4SiC4 powder.

[0064] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 130 ppm, the crystallite size was 1220 Å, and the particle size distribution span value was 2.2. Example 5

[0065] 20 mass% of expanded graphite was added as a secondary material of the carbon source. That is, the carbon source was 80 mass% of pre-heat-treated carbon black and 20 mass% of expanded graphite. Other than this, the same method as in Example 1 was used to obtain Al4SiC4 powder.

[0066] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 130 ppm, the crystallite size was 1244 Å, and the particle size distribution span value was 2.4. Example 6

[0067] Activated carbon was added at 5 mass% as a secondary carbon source. That is, the carbon source was 95 mass% of pre-heat-treated carbon black and 5 mass% of activated carbon. Other than this, the same method as in Example 1 was used to obtain Al4SiC4 powder.

[0068] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 120 ppm, the crystallite size was 1168 Å, and the particle size distribution span value was 1.9. Example 7

[0069] Activated carbon was added as a secondary carbon source at 20 mass%. That is, the carbon source was 80 mass% of pre-heat-treated carbon black and 20 mass% of activated carbon. Other than this, the same method as in Example 1 was used to obtain Al4SiC4 powder.

[0070] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 140 ppm, the crystallite size was 1212 Å, and the particle size distribution span value was 1.8. Comparative Example 1

[0071] The carbon source was 100 mass% needle coke. Other than this, the same method as in Example 1 was used to obtain Al4SiC4 powder.

[0072] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The sulphur content was 160 ppm, the crystallite size was 1073 Å and the particle size distribution span value was 2.3. Comparative Example 2

[0073] The carbon source was 100 mass% activated carbon. Other than this, the same method as in Example 1 was used to obtain Al4SiC4 powder.

[0074] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 180 ppm, the crystallite size was 1149 Å, and the particle size distribution span value was 1.8. Comparative Example 3

[0075] The carbon source was 50 mass% of preheat-treated carbon black, 25 mass% of needle coke, and 25 mass% of expanded graphite. Other than this, the same method as in Example 1 was used to obtain Al4SiC4 powder.

[0076] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 160 ppm, the crystallite size was 1176 Å, and the particle size distribution span value was 2.4. Comparative Example 4

[0077] The carbon source was 50 mass% of preheat-treated carbon black, 25 mass% of needle coke, and 25 mass% of activated carbon. Other than this, the same method as in Example 1 was used to obtain Al4SiC4 powder.

[0078] The obtained Al4SiC4 powder I Al4C3 / I Al4SiC4 is 0, I G / I Al4SiC4 The average particle size was 0, the sulfur content was 180 ppm, the crystallite size was 1203 Å, and the particle size distribution span value was 1.7. The above results are summarized in Table 2.

[0079] [Table 2]

[0080] In the Al4SiC4 powders obtained in Examples 1 to 7, no peaks of Al4C3 were observed in the powder X-ray diffraction (I Al4C3 / I Al4SiC4is 0), and no diffraction peaks of graphite are observed (I G / I Al4SiC4 The content of Al4C3 was 0), and the sulfur content was 150 ppm or less. In other words, the Al4SiC4 powder was substantially free of Al4C3, graphite, and sulfur.

[0081] In Examples 2 to 7, the sulfur content was slightly increased compared to Example 1 because a secondary material was added to the carbon source.

[0082] In Example 5, the crystallite size is large because the crystallites of Al4SiC4, from which expanded graphite, which is crystalline carbon, is synthesized, are grown.

[0083] On the other hand, in the Al4SiC4 powder obtained in Comparative Example 1, a graphite diffraction peak was observed in the powder X-ray diffraction (I G / I Al4SiC4 The sulfur content of needle coke was 2.89), and the sulfur content was 160 ppm. This is presumably because the sulfur content of the needle coke was high, and the sulfur in the needle coke partially reacted with the aluminum in the raw material, leaving a small amount of needle coke remaining, and the small amount of unreacted needle coke was partially graphitized and remained.

[0084] The Al4SiC4 powder obtained in Comparative Example 2 had a sulfur content of 180 ppm. This is because the sulfur content derived from the activated carbon was high.

[0085] The Al4SiC4 powder obtained in Comparative Example 3 had a sulfur content of 160 ppm. This is because the amount of the secondary material of the carbon source was large.

[0086] The Al4SiC4 powder obtained in Comparative Example 4 had a sulfur content of 180 ppm. This was because the amount of the secondary material of the carbon source was large.

Claims

【Request 1】 Al at 2θ=55.1° measured by powder X-ray diffraction 4 C 3 The integrated intensity I of the diffraction peak Al4C3 (cps deg) and Al at around 2θ = 56.0° 4 SiC 4 The integrated intensity I of the diffraction peak Al4SiC4 Ratio I to (cps・deg) Al4C3 / I Al4SiC4 is 0.1% or less, and the sulfur content is 150 mass ppm or less; Al at 2θ=31.7° measured by powder X-ray diffraction 4 SiC 4 Al having a crystallite size of 1000 to 1500 Å calculated from the diffraction peak of 4 SiC 4 Composition or Al 4 SiC 4 powder. 【Request 2】 The integrated intensity I of the graphite diffraction peak at around 2θ = 26.5° measured by powder X-ray diffraction G (cps deg) and Al at around 2θ = 56.0° 4 SiC 4 The integrated intensity I of the diffraction peak Al4SiC4 Ratio I to (cps・deg) G / I Al4SiC4 2. The Al content of claim 1, wherein the Al content is 0.01% or less. 4 SiC 4 Composition or Al 4 SiC 4 powder. 【Request 3】 In the volume-based particle size distribution, the difference between the cumulative 90% particle size and the cumulative 10% particle size is divided by the cumulative 50% particle size (D 90 -D 10 ) / D 50 The Al content according to claim 1 or 2 is 1.7 to 2.

5. 4 SiC 4 powder.

Citation Information

Patent Citations

  • Method for producing aluminum silicon carbide

    JP2020029390A

  • METHOD FOR PRODUCING Al4SiC4

    JP2020100522A

  • Method of manufacturing sliding nozzle plate

    JP2020163458A